Clinical and Onychoscopic Features of Benign and Malignant Conditions in Longitudinal Melanonychia in the Thai Population: A Comparative Analysis - Kungvalpivat P; Rojhirunsakool S; Chayavichitsilp P; Suchonwanit P; Wichayachakorn CT; Rutnin S (Dove Medical Press, 2020)
Pintusorn Kungvalpivat,1 Salinee Rojhirunsakool,1,2 Pamela Chayavichitsilp,1 Poonkiat Suchonwanit,1 Chanitwan T Wichayachakorn,1 Suthinee Rutnin1 1Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 2Skin Center, Srinakharinwirot University, Bangkok, ThailandCorrespondence: Suthinee RutninDivision of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, ThailandTel +66-2-2011141Fax +66-2-201-1211 Ext 4Email suthinee.rutnin@gmail.comBackground: Longitudinal melanonychia can arise from many underlying conditions, both benign and malignant. Practitioners tend to be reluctant to perform a biopsy of this condition due to procedure-related pain and the possibility of permanent nail dystrophy. Onychoscopy has become a useful tool to provide a provisional diagnosis and assist in deciding on a nail biopsy.Objective: To investigate and differentiate the clinical and onychoscopic features of subungual melanoma (SUM)/subungual melanoma in situ (SMIS) and other benign melanocytic conditions (BM).Materials and Methods: In this cross-sectional study, a total of 32 cases of longitudinal melanonychia were examined, and baseline characteristics were recorded. Onychoscopic pictures were taken by handheld dermoscopy with 10x and 50x magnification. A biopsy was then performed in each case, and a pathological diagnosis was obtained.Results: Of the 32 cases, 6 were diagnosed with SMIS and 26 with BM (21 simple lentigines, 5 junctional nevi). The median age was significantly higher among the SMIS group (56 vs 31 years) (p = 0.034). Regarding onychoscopic findings, cases with SMIS were significantly associated with a greater band width percentage (p = 0.014), multicolor presentation (p = 0.005), the presence of granular pigmentation (p = 0.034), and micro-Hutchinson’s sign (p = 0.015). In addition, subungual hyperkeratosis, a newly recognized onychoscopic feature, was more significantly associated with SMIS in comparison to BM (p = 0.002).Conclusion: Onychoscopy provides useful information to aid in the differential diagnosis of longitudinal melanonychia. From our study, onychoscopy can be utilized to assist in making a decision whether to perform a biopsy in patients with longitudinal melanonychia suspicious of malignant melanocytic conditions.Keywords: longitudinal melanonychia, subungual melanoma, subungual melanoma in situ, onychoscopy, dermoscopy